EVALUATION OF ANTI-INFLAMMATORY ACTIVITY OF JOINTS KARE A POLYHERBAL FORMULATION - EXPERIMENTAL STUDY - Verma, Amnish; Lal Sharma, Roop (International Journal of Ayurveda and Pharma Research, 2015)
The Anti-inflammatory activity of JOINTS KARE, a poly herbal ayurvedic formulation developed and studied in the Jammu Institute of Ayurveda and Research Pharmacy with the technical assistance from Indian Institute of Integrative Medicine, the study was performed on albino rats of carrageenan induced model. 20 healthy albino rats were selected randomly and divided into five groups. The inflammatory reaction is readily produced in rats in the form of paw oedema with the help of irritants. Here the rats of treated Group II, III, IV and V were administered orally with Ibuprofen solution, Joints Kare 125mg/Kg Body wt, Joints Kare 250mg/Kg Body wt, Joints Kare 500mg/Kg Body wt, respectively one hour before injecting 1%w/v suspension of carrageenan (0.1 ml) into the sub plantar region of left hind paw of all the five groups.Paw volume of all 20 rats were measured soon after injecting carrageenan. The volume was again measured after 1, 2, 3, 4 & 24 hrs in all the five groups of rats. The change in paw volume of Group I was compared with Group II, III, IV & V. Also the treated Group II, III, IV, V were also compared in between and expressed as percentage oedema inhibition by the drug. Results of the present study are based on the oedema of hind paw of rats of all five groups measured after 1hr, 2hrs, 3hrs, 4hrs and 24hrs after carrageenan injection. The maximum activity of all trial Groups were observed during first and second hr. and the results are significant (P <0.005) and are comparable to standard Ibuprofen. Highest percentage oedema Inhibition was seen after 1 & 2 hrs. Summarizing the above it is concluded that Joints Kare has showed its extreme utility or significance on the inflammation probably because of its excellent activity of inhibiting the both early released and late released mediators which is rarely seen in any anti-inflammatory formulation.